2014
DOI: 10.1111/cge.12468
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for recruitment of relatives of BRCA mutation carriers to a genetic testing program in the Bahamas

Abstract: The prevalence of BRCA1 and BRCA2 mutations among unselected breast cancer patients in the Bahamas is 23%. It is beneficial to advise relatives of mutation carriers that they are candidates for genetic testing. Women who test positive are then eligible for preventive interventions, such as oophorectomy. It is not clear how often relatives of women with a mutation in the Bahamas wish to undergo genetic testing for the family mutation. Furthermore, it is not clear how best to communicate this sensitive informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…In the Bahamas, Trottier et al reported that when the proband was the route of communication fewer than 20% of at risk relatives came for testing. 29 Consequently, it is important that future studies which evaluate genetic testing among underserved populations also address uptake of cancer risk management options and sharing of test results with family members in order for the full potential of genetic testing for BRCA1 and BRCA2 to be realized.…”
Section: Discussionmentioning
confidence: 99%
“…In the Bahamas, Trottier et al reported that when the proband was the route of communication fewer than 20% of at risk relatives came for testing. 29 Consequently, it is important that future studies which evaluate genetic testing among underserved populations also address uptake of cancer risk management options and sharing of test results with family members in order for the full potential of genetic testing for BRCA1 and BRCA2 to be realized.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of 115 patients with BRCA1/2 mutations, 77% of patients informed at least one relative about their genetic testing results, but only half of relatives underwent testing [12]. Other studies report that as few as 9% of atrisk relatives pursued testing [13,14]. Thus, identifying barriers to, and strategies to improve, CGT could improve cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The survey population included female residents in the Bahamas for whom a mutation had been detected by genetic testing through the course of several studies conducted between 2004 and 2012 (Akbari et al., ; Trottier et al., , ). When a mutation was identified in a family, genetic counseling and testing was offered to other at‐risk women in the family (Trottier et al., ). Women were recruited to these studies from public and private sources, including clinics in Freeport and Nassau in the Bahamas as described.…”
Section: Methodsmentioning
confidence: 99%